2009
DOI: 10.1021/jm9013086
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Rhodacyanine (SJL-01) Possessing High Efficacy for Visceral Leishmaniasis (VL)

Abstract: Anti-Leishmania in vitro and in vivo activities of various rhodacyanine derivatives have been examined. Among them, the fluorinatied variant SJL-01 (8) showed IC(50) of 0.011 microM against Leishmania donovani strain MHOM/ET/67/L82 (selective index of >15000) and 95-97% inhibition against L. donovani strain MHOM/ET/67/HU in female BALB/c mice by 1.3-12.5 mg/kg x 5 iv administrations. Negative results on chromosomal aberration test and in vitro micronucleus test suggest that compound 8 is a hopeful candidate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…In addition to the antileishmanial activity reported in the study by Sharlow et al, a series of papers have also described the antiprotozoal activity of cyanine dyes (21,22,(34)(35)(36)45). These reports mainly focused on the antimalarial effects of rhodanine-containing cyanines (rhodacyanines) and showed that these agents display nanomolar potency against Plasmodium falciparum in vitro (21,22,34,35) and good in vivo efficacy against murine P. berghei infections (21,22,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the antileishmanial activity reported in the study by Sharlow et al, a series of papers have also described the antiprotozoal activity of cyanine dyes (21,22,(34)(35)(36)45). These reports mainly focused on the antimalarial effects of rhodanine-containing cyanines (rhodacyanines) and showed that these agents display nanomolar potency against Plasmodium falciparum in vitro (21,22,34,35) and good in vivo efficacy against murine P. berghei infections (21,22,35).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, this class was not pursued further because the sole cyanine compound investigated was slightly less potent in vitro against P. falciparum erythrocytestage parasites and L. major promastigotes compared to some tricyclic rhodacyanines studied. Two rhodacyanines displayed midnanomolar potencies against intracellular L. donovani, and treatment of L. donovani-infected mice with one of these rhodacyanines at a dose of 1.3 mg/kg/day ϫ 5 by the intravenous route resulted in 95% inhibition of liver parasitemia (45). In our study, cyanines 2312703, 16196319, and 16196223 all displayed midnanomolar potency against both intracellular L. donovani and intracellular L. amazonensis, while 123859 was highly active against intracellular L. donovani but less potent against intracellular L. amazonensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plates were kept at room temperature. After 24 h, 20 µl of Alamar blue (12.5 mg of resazurin dissolved in 100 mlof distilled water) (Yang et al, 2010) was added to each of the wells. Absorbance of the resulting mixture was measured after 48 h at a wavelength of 540 and 630 nm using Enzyme Linked Immuno Sorbent Assay (ELISA) plate reader (Al-Nasiry et al, 2007).…”
Section: In Vitro Antipromastigote Assaymentioning
confidence: 99%
“…The uptake of the rhodacyanines in mitochondria may play a key role in inhibiting malaria diseases. 36,[56][57][58][59][60][61] The causal pathogenic parasites of NTDs, such as Trypanosoma spp. and Leishmania spp., belong to the Trypanosomatidae family in the Euglenozoa phylum.…”
Section: )mentioning
confidence: 99%